(untitled) (Acta Scientiarum. Animal Sciences, 2025)
In intensive livestock farming is important that cattle have high space allowance and continuous availability of food to improve animal welfare. It is possible that such conditions may improve fat quality. The aim of this work was to evaluate the impact of concentrate diets supply alternatives and space allowances in beef finishing on meat nutritional quality through fatty acid profile analysis and healthy fat indices determination Forty-eight Hereford steers aged 7.9 months and 175.0 ± 19.8 Kg body weight (BW) were allocated into four treatments in a 2Ã—2 factorial arrangement: 100BF (food supply in feed bunks and 100 m2 animal-1), 100SF (food supply in self-feeders and 100 m2 animal-1), 10BF (food supply in feed bunks and 10 m2 animal-1), 10SF (food supply in self-feeders and 10 m2 animal-1). The fatty acid profile was measured and the healthy fat indices - atherogenic index (AI), thrombogenic index (TI), hypocholesterolemic/Hypercholesterolemic fatty acid ratio (h/H) and healthy fatty index (HFI)- were obtained. Treatments with self-feeders showed better AI, TI, h/H and HFI compared to groups with daily supply (0.5 vs. 0.6; 1.5 vs. 1.7; 1.6 vs. 1.4 and 1.6 vs. 1.7 respectively). In conclusion, animal production under comfortable conditions can contribute to the nutritional quality of meat.